New Method of Calculating the Excess Amount of Soft Tissues of the Orbit in Patients with Endocrine Ophthalmopathy when Planning Operations - D. V. Davydov (Oftalʹmologiâ, 2019)
Objective. Improving the efficiency of the operation of orbit decompression in patients with endocrine ophthalmopathy through the development of a new method for calculating an excess volume of soft tissues of the orbit. Patients and methods. A total of 16 patients with edematous exophthalmos were examined, 7 of them were men and 9 women were aged 28 to 62 years (mean age 39 ± 8 years). All patients underwent surgery — simultaneous internal decompression of the orbit for bilateral exophthalmos with endocrine ophthalmopathy (EO). Before surgery and after 6 months. after surgery, patients were performed MSCT control. According to the method developed by us with the help of standard software MSCT, before the operation, calculations were made and the magnitude of the postoperative standing of the eyeballs was planned. Results. As a result of the operations performed, we removed the estimated amount of adipose tissue and achieved the predicted result. Error in the calculations amounted to 0,1(+/-0,1) mm, which may be due to inaccurate labeling during planning. Findings. The developed calculation method makes it possible to calculate the planned volume of the removed fatty tissue before the operation with the minimum error, without using complex mathematical calculations and without resorting to the help of additional equipment and software.